Self-assessment in medicine and surgery - SHARMA, Neel (Crash course, 2009)
Crash Course is a complete revision guide designed specifically to save you time by providing everything you could be asked in the exam in one place. Each book in the series has been specially written either by senior medical students or junior doctors carefully supervised by faculty advisors to ensure that it exactly matches your needs by having been prepared by someone who has just been in the exam situation. Fully up-to-date with improved layout, this brand new edition to the Crash Course series will help you tackle both the new form of assessment as well as the traditional style of examination. Questions covering all common medical and surgical presentations are included in MCQ and EMQ formats with relevant, concise explanations given as answers. Designed to increase your confidence as you approach your finals, this book is ideal for all MBBS students studying at both UMAP and traditional schools of medicine.